PRELIMINARY ANALYSIS OF NUCLEAR TRANSCRIPTOME REVEALED THE EXTENSIVE NUCLEAR-ENRICHED SUBCELLULAR DISTRIBUTION PATTERN OF TRANSPOSABLE ELEMENT-DERIVED TRANSCRIPTS IN RICE - L. Zeng，X. Tan; S. Hu; and Y. Luo (Journal of Animal and Plant Sciences, 2022)
The complexity and its functional consequence of nuclear transcriptome have come to be documented in mammal cells. However, little is known about plantnuclear transcriptome. In this study, we explored the complexity of rice nuclear transcriptome via the profiling of whole protoplasts and isolated nucleus using rRNA-depleted RNA-seq strategy. The expression characteristics of the long non-protein coding RNAs,transposable element-related genes and conventional protein coding genes were investigated. These analysesfound that the proportion of expressed TE-related genes and reads mapped to these genes in nucleus were four time of that in protoplasts. In particular, no obvious nuclear-enriched expression pattern of lncRNAs or conventional protein coding genes was observed. Therefore, the extensive transcription of TE-related genes was the major contribution of the larger diversity of nuclear RNA species. Further muti-tissues comparative transcriptome analysis indicated that the transcription of TE-related genes, especially for nuclear-specific expressed TE-related genes defined in this study, was likely to be underestimated by conventional bulk RNA-seq. Furthermore, Gene Ontology functional enrichment analysis indicated that some nuclear abundant lncRNAs were co-expressed with nuclear-located RNA binding proteins. Together, the global features of rice nuclear transcriptome will prompt the functional characterization of the nuclear-expressed TE-related genes and lncRNAs.
Keywords: Nuclear transcriptome; Rice; RNA-seq; long non-protein coding RNAs; transposable element-related genes